2009
DOI: 10.1111/j.1365-2796.2009.02159.x
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome

Abstract: Restless legs syndrome (RLS) is a common neurological sensory-motor disorder that is characterized by intense restlessness and unpleasant creeping sensations deep inside the lower legs. Symptoms appear when the legs are at rest and are worst in the evening and at night. They force patients to keep moving their legs, and often to get out of bed and wander about. Periodic limb movements (PLMS) are also common during sleep amongst those suffering from RLS, and sleep efficiency is severely reduced. There are idiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
174
2
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(205 citation statements)
references
References 105 publications
(153 reference statements)
12
174
2
17
Order By: Relevance
“…Several case series have indicated that RLS patients with anemia or low serum ferritin may benefit from iron treatment [8][9][10]. This study excluded subjects who were anemic and included subjects with a broad range of ferritin values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case series have indicated that RLS patients with anemia or low serum ferritin may benefit from iron treatment [8][9][10]. This study excluded subjects who were anemic and included subjects with a broad range of ferritin values.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with RLS symptoms and a peripheral iron deficiency, treatment with oral iron will improve, or in some cases eliminate the RLS symptoms [8][9][10]. What is less clear is whether or not increasing the peripheral iron load in patients, who have otherwise "normal" serum iron values, will improve RLS symptoms and change iron in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this SCI animal model, a decreased sleep efficiency, an increase in the number of arousals and in the presence of PLMs have been reported in clinical situations. 9 Iron concentration is another factor associated with SCI and PLM. Liu et al 10 analyzed the total concentrations of iron, protein carriers and low-weight iron in rats with SCI between the T3 and L1 vertebrae.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies had participants who completed self-administered questionnaires [17][18][19][20][25][26][27], another seven conducted face to face interviews [16, 21-24, 26, 29, 31], and three studies did not specify how data was collected [28,30,31].…”
Section: Prevalence Of Wed/rls During Pregnancymentioning
confidence: 99%
“…This yielded 131 articles in Pub Med. Of these, 16 were peer-reviewed articles specifically dealing with the prevalence of WED/RLS during pregnancy and were written in the English language; these 16 articles, spanning 1945 -2012, were included in this review ( Table 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Prevalence Of Wed/rls During Pregnancymentioning
confidence: 99%